The myth of white skin: a postcolonial review of cosmetics ads in Indonesia - Wulan, Roro Retno (2017)
Cosmetics industry created the beauty myth for women through advertising.A cosmetic ad in Indonesia has spread a new concept of white skin: East Asia beauty myth.The white concept of Asia white skin basically derived from colonial legacy.The purpose of the research was analyzing the beauty myth in Indonesia ads using postcolonial perspective. The principal result brought the discourse analysis and postcolonial perspective a new insight in communication research. Particularly on media and cultural studies. Major conclusions showed that the beauty myth since the Dutch colonial period never been change.The main concept is always in colonialism’s idea: “white is better”. The West is better than the East.